Lihir Destiny Cultural Responses to Mining in Melanesia - A. Bainton, Nicholas (Asia-Pacific Environment Monograph, 2010)
The people of the Lihir Islands in Papua New Guinea have long held visions of a prosperous new future, often referred to by local leaders as the 'Lihir Destiny'. When large-scale gold mining activities commenced on the main island of Lihir in 1995, many hoped that this new world had finally arrived. The Lihir Destiny provides a nuanced account of the social structural and cultural transformations engendered by large-scale resource extraction. Tracing the history of Lihirian engagement with outside forces, from the colonial period through to recent mining activities, this book brings new light to bear on the bigger question of what 'development' means in contemporary Melanesia. The Lihir Destiny explores how Lihirian leaders devised future plans for a cultural revolution based upon the maximisation of mining activities and the influential philosophies of the Personal Viability movement. However, reaching the 'Lihir Destiny' is no simple affair, and many Lihirians find themselves negotiating divergent formulations of culture, sociality and economic engagement. The Lihir Destiny will appeal to readers interested in the social impacts of large-scale resource development, the processes of cultural continuity and change and the ways in which modernity is configured in local terms.